MICROLEAKAGE OF COMPOSITE RESTORATIONS UNDER DIFFERENT PROTOCOLS OF PREPARATION, ADHESIVE PREPARATION AND CARIOUS CAVITIES DEPTH - Lakhtin, Yurii; Hryhoriev, Denys (Eastern Ukrainian Medical Journal, 2026)
Aim: To assess the microflow of composite restorations in teeth prepared according to various protocols of preparation (traditional with rotary instruments and air abrasion), adhesive preparation (tissue etching and without etching) and the depth of carious lesions. Material and methods: The study was carried ouconducted on 180 pre-prepared extracted teeth, divided into 4 groups of 45 samples each: GI, GII, GIIII, GIV. On the occlusal surface of the teeth, cavities of different depths were formed. In groups GI, GII according to the technique of traditional preparation with the use of rotary tools, in GIII, GIV – according to the technique of air abrasion. In GI and GIII groups, tissue etching was not performed, in the GII and GIV groups, 37 % phosphoric acid gel was used for etching. A one-component light-curing adhesive Charisma GLUMA® Bond 5 was put into the prepared cavities GI, GII, GIII, GІV, which then were filled with a light-hardening hybrid composite Charisma “SMART”. All samples were subjected to thermal cycling, varnished, immersed in a 1% aqueous solution of methylene blue for 24 hours, separated along the axis, and studied the penetration of the dye through a microscope. Results: Data comparisons within groups with different cavity preparation protocols showed a difference in the mean values of the depth of dye penetration in each group, but it is not always statistically significant. Differences were recorded when comparing groups according to adhesive preparation protocols. The use of air abrasion in GIII reduced the restorations microleakage rates compared to GI (p ˂ 0.05). In GIV there was a similar situation in comparison with GІI, but not significant (p ˃ 0.05). Conclusions: The state of microleakage of restorations is influenced by both the cavities depth and the protocols of preparation and adhesive preparation, with the latter having a stronger effect. Mutually, these factors do not affect microleakage. Lower microleakage rates are recorded during preparation with the air abrasion technique.